Phenotypic variability of Linum usitatissimum L. accessions under the conditions of the Northern Trans-urals - K. P. Korolev; N. A. Bome; N. N. Kolokolova (Труды по прикладной ботанике, генетике и селекции)
Background. One of the ways to increase flax production is to expand cropping areas, including nontraditional ones. To solve this problem, it is necessary to carefully select cultivars that can produce stable high yields and have competitive raw material quality. The aim of this study was to identify the adaptability potential of flax accessions and select sources of valuable properties for their use under the conditions of the Northern Trans-Urals.Materials and methods. Sixty flax accessions were studied in the fields of the south of Tyumen Province in 2017–2020. Phenotypic screening was performed according to the published lists of descriptors, taking into account outdoor seed germination, plant height, seed yield, flax straw, retted stalks, and fiber. Statistical data processing included the multivariate analysis of variance and correlation analysis. Environmental screening was performed according to S. A. Eberhart, W. A. Russell.Results and conclusion. Based on the long-term data, sources of traits were identified: 4 for outdoor seed germination, 4 for plant height, 11 for the duration of the growing season, 21 for straw yield, 19 for the yield of retted stalks, 9 for seed yield, 6 for total fiber yield, and 5 for 1000 seed weight. The manifestation of traits was shown to be largely induced by the impact of the environment factor and the complex genotype × environment interaction. On the basis of screening results, 12 accessions were selected. The correlation analysis helped to find out that on average over the years of research there were high and stable direct relationships of the yield of straw (r = 0.73–1.00) and retted stalks (r = 0.68–1.00) with plant height. Under relatively favorable conditions for plant growth and development during the growing seasons of 2017 and 2020, the influence of outdoor seed germination on plant height (r = 0.62–1.00), straw yield (r = 0.78–1.00), and seed yield (r = 0.52–0.91) increased.